(untitled) (Fiep Bulletin - online, 2012)
The sports evolve as the speed, new modalities, rules, technique, tactics to play, consequently influence the behavior and action during this practical. The familiar relation, the diversity of cultural and social linkings influences directly in the sporting being. For pupils, sporting practitioners or athlete, the ethics and the moral many times clearly are not displayed or almost always they are preceded of an informal learning. The level of requirements to deal with this reality seems to the professional of the physical education an arduous thick partition wall to transpose, due the barrier to play loyally or to use artifices to be successful. From this work was objectified to understand characteristics of the ethics and moral, being standed out the importance of the sporting values and as to carry through pedagogically effective works with intention to improve the ethics and sports moral. Through qualitative research with theoretical and practical references, one perceives that it has possibilities to very reach and to improve the practical sports in relation to the ethics and the moral. People who carry through practise it of sports generally are interested in the game by itself, she has tension and satisfaction generated during the practical one, and many times forgetting the importance it respect and the valuation to the next one. It fits to the professional attention the trends of participation, behavior of the players and behaviors, therefore the ethical and moral dimension related the sports values requires recognition of operating subjective aspects in the social culture. If ethical it indicates norms and moral the way of if holding in its group, the professional of physical education needs to identify the characteristics of the involved group and to carry through positive actions for these two phenomena: through cooperative games, cultural artistic activities, bigger familiar envolvement. It is concluded through that we can insert the actions found in diverse sports areas or does not stop improving the ethics and moral consecutively and the society where we live.